PERLINDUNGAN HUKUM TERHADAP ANAK KORBAN TINDAK PIDANA PELECEHAN SEKSUAL - SARUDI SARUDI (GANEC SWARA, 2024)
To the effect of inscriptive it is subject to be know protection principle sentences to sexual abuse victim child base child protection laws and know LPA roles in give protection to sexual abuse victim child. Observational type that is utilized is observational Normative Empiric. Empirical research, are a methodic functioning law research to see law in real mean and analyzing how works it law at environmentally Society. Can be said that jurisdictional research that taken from by aught fact in a society. Of description upon can be concluded that sexual abuse no is gone, added by all pro con at in it. Sexual abuse really frequent happening on notably, Female and child, but doesn't close that possible boy also there is that experiences sexual abuse. Severally of sexual abuse victim consciously comes directly report instance and consul goes to psychologist. But a lot of sexual abuse case that doesn't be detected because victim it shame overshoot to tell that thing to others by takes on alone charges. There is factor even other causative averse victim consults since having cold feet to reveal tells on others, caused by cost limit, time and place and culture factor,  psychological another.